The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10068-017-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

Fucosterol inhibits adipogenesis through the activation of AMPK and Wnt/β-catenin signaling pathways

Abstract: Fucosterol is a sterol constituent primarily derived from brown algae. Recently, the antiadipogenic effect of fucosterol has been reported; however, its molecular mechanism remains to be studied. Fucosterol effectively upregulated the phosphorylations of both adenosine monophosphate (AMP)-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC), and downregulated the expression levels of lipogenesis-related factors. Moreover, fucosterol activated the major components of the Wnt/β-catenin signaling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The modulation of AMPK can inhibit the progression of adipogenic differentiation. Fucosterol derived from brown algae suppresses adipogenesis via AMPK activation [40], while Arctigenin found in Arctii Fructus suppresses adipogenic differentiation via the activation of AMPK and reduces obesity in high-fat diet-induced obese mice [41]. We observed that DMBQ increases phosphorylation of AMPK while downregulating mature SREBP-1 and PPARγ expression in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 64%
“…The modulation of AMPK can inhibit the progression of adipogenic differentiation. Fucosterol derived from brown algae suppresses adipogenesis via AMPK activation [40], while Arctigenin found in Arctii Fructus suppresses adipogenic differentiation via the activation of AMPK and reduces obesity in high-fat diet-induced obese mice [41]. We observed that DMBQ increases phosphorylation of AMPK while downregulating mature SREBP-1 and PPARγ expression in 3T3-L1 adipocytes.…”
Section: Discussionmentioning
confidence: 64%
“…In the ELISA results, the expression of ADPN was increased in each group compared with that in the model group, indicating that FRLE can activate the AMPKα phosphorylation pathway by increasing the expression of ADPN. After the AMPKα phosphorylation level was increased, the downstream molecule ACC phosphorylation pathway was also activated, and the ACC pathway was inhibited (Song et al., 2017). Meanwhile, the expression of related downstream lipid synthesis indexes, such as SREBP‐1c, was inhibited (Zhang et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism of action: Several studies have investigated both in vitro and in vivo the potential health benefits and the underlying pharmacological mechanisms of phytosterols, beyond the well-known cholesterol-lowering effect, obtained by competition with cholesterol upon intestinal absorption [ 119 ]. The phytosterol fucosterol exerts hepatoprotective, anti-obesity, anti-diabetic, and antihypertensive activities [ 46 , 78 , 79 ]. Moreover, it has been demonstrated that it inhibits adipogenesis and adipocytes differentiation by diverse molecular mechanisms [ 78 , 79 , 80 ].…”
Section: Bioactive Compounds Of Brown Seaweedsmentioning
confidence: 99%
“…The phytosterol fucosterol exerts hepatoprotective, anti-obesity, anti-diabetic, and antihypertensive activities [ 46 , 78 , 79 ]. Moreover, it has been demonstrated that it inhibits adipogenesis and adipocytes differentiation by diverse molecular mechanisms [ 78 , 79 , 80 ]. In particular, the downregulation of Peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α (C/EBPα) leads to a reduction in lipid accumulation inside adipocytes [ 79 ].…”
Section: Bioactive Compounds Of Brown Seaweedsmentioning
confidence: 99%